Fourier Series of the Periodic Bernoulli and Euler Functions - Cheon Seoung Ryoo; Hyuck In Kwon; Jihee Yoon; Yu Seon Jang (Abstract and Applied Analysis)
We give some properties of the periodic Bernoulli functions and study the Fourier series of the periodic Euler functions which are derived periodic functions from the Euler polynomials. And we derive the relations between the periodic Bernoulli functions and those from Euler polynomials by using the Fourier series.